Integrated Service Pos Program Outcomes for Elderly in Kebonsari Village - Suharjo, Ari; Sukmana, Hendra (Indonesian Journal of Cultural and Community Development, 2024)
Background: The elderly population has unique health needs requiring specialized services. Specific Background: This study investigates the implementation of the Posyandu Lansia Wijaya Kusuma program, focusing on operational procedures and challenges in a rural context. Knowledge Gap: There is a lack of understanding regarding specific obstacles faced in implementing such health programs in similar communities. Aims: This research aims to evaluate program operations and identify hindering factors. Results: Data from interviews and participatory observations indicate a structured Standard Operating Procedure (SOP) for the Posyandu Lansia, facilitating essential health services. While the program follows a clear framework, operational barriers impact service delivery. Novelty: This study highlights the importance of adhering to SOPs to enhance healthcare outcomes for the elderly, offering insights distinct from previous research emphasizing SOP improvements. Implications: Findings emphasize the need to optimize health services for the elderly, informing policy decisions to improve healthcare systems in rural areas and advocating for ongoing evaluation of health programs to address evolving elderly needs. Highlights : Structured SOP: The program follows a clear Standard Operating Procedure for service delivery. Operational Barriers: Identified challenges impact the effectiveness of health services for the elderly. Policy Implications: Findings inform improvements in rural healthcare systems and program evaluation. Keywords: elderly care, health services, Posyandu Lansia, implementation, rural health